A rapid review of the red eye. Issue 7 (July 2022) - McSwigan, Tara M.; Beck, David; Farkas, Deborah
ABSTRACT: The red eye is a common presenting complaint among patients. Although assessment may seem intimidating, clinicians who are mindful of the patient's anticipated history and physical examination findings should be able to accurately diagnose and manage common conditions, identify ocular emergencies, and expedite care.